2018
DOI: 10.1016/j.gaitpost.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile Feedback Alters Dynamics Of Static Postural Control In Persons With Parkinson’s Disease But Not Older Adults At High Fall Risk

Abstract: Considering the effects of vibrotactile feedback were dependent on the population and stance condition, designing an optimal therapeutic regimen for balance training should be carefully considered and be specific to a target population. Furthermore, our results suggest that explicit instructions on how to respond to the vibrotactile feedback could affect training outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…In line with several previous studies [ 11 , 23 , 27 , 51 ], the results obtained in this study suggest that feedback mechanism–based interventions are satisfactory. The pilot experiment showed that subjects applied significantly more accurate loads on the forearm crutches after only a few minutes, or even a few seconds in some cases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with several previous studies [ 11 , 23 , 27 , 51 ], the results obtained in this study suggest that feedback mechanism–based interventions are satisfactory. The pilot experiment showed that subjects applied significantly more accurate loads on the forearm crutches after only a few minutes, or even a few seconds in some cases.…”
Section: Discussionsupporting
confidence: 92%
“…This is the basic principle underlying feedback mechanisms [7,9,10]. This paper focuses on extrinsic feedback, which is provided by external sources [11,12]. The wide range of well-known feedback technologies include visual [5,[13][14][15], acoustic [16][17][18], and haptic [11,16,19] technologies, which are usually adapted to each individual user in a coherent manner [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haptic feedback systems are generally composed of an actuation system providing vibratory cues to the patient, a sensory system collecting measurements about the user, and a processing unit running an algorithm that suggests when to activate actuators [ 16 , 17 ]. The actuators are usually positioned around the trunk, hips, or head and can number from two to eight, depending on the body position [ 16 , 17 , 18 ]. The sensors usually integrated into these systems are inertial measurement units (IMU), commonly positioned near ankles, lower trunks, hips, knees, shins, or feet [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Postural control is one of the most important capacity for the elderly. Multiple studies have found that postural control plays a crucial role in keeping balance and preventing falls [9][10][11]. Cardiopulmonary endurance is also regarded as one of the most important capacity for older individuals.…”
Section: Introductionmentioning
confidence: 99%